LESÕES DE PELE ASSOCIADA AO DISPOSITIVO DE ACESSO VASCULAR: PROTOCOLO DE REVISÃO DE ESCOPO. - Rocha, Patrícia Kuerten; Ullman, Amanda; dos Santos, Luciano Marques; da Silva, Thiago Lopes; da Silva Moura, Jefferson Wildes; de Moura, Sayonara Stéfane Tavares (Enfermagem Atual in Derme)
Objective: To report the protocol of a scoping review that aims to map and synthesize the available scientific evidence regarding the definitions of medical adhesive-related skin injuries and catheter-associated skin injuries at intravenous device insertion sites. Methods: This is a scoping review protocol developed in five stages: Identification of the research question, using the Population, Concept, and Context strategy; Identification of relevant studies, in which the search will be conducted in the main health-related databases; Study selection, which will involve initial screening, study selection, and data extraction using the Covidence platform; Data analysis, which will include the characterization and description of the articles; and Grouping, summarization, and presentation of results in a narrative and descriptive quantitative format, integrating the findings with the objectives of the scoping review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.